Landscape of augmented reality research: A bibliometric analysis - Fatmawaty Fatmawaty; Duden Saepuzaman; Dadi Rusdiana (Universitas PGRI Kanjuruhan Malang, 2026)
This study aims to examine the trends, contributions, and impact of Augmented Reality research, particularly in physics education, from 2006 to 2025. The study employs a bibliometric analysis approach using the Scopus database. The analysis was conducted with the aid of several software tools, including R Studio with the bibliometric and biblioshiny packages, VOS viewer, and Microsoft Excel. The findings indicate a significant increase in research productivity over the past two decades. Indonesia and the United States (USA) emerged as the two main contributing countries, with Universitas Negeri Semarang and the International Information Technology University identified as the most productive affiliations. Daineko, Y. A., stands out as a leading author, demonstrating strong research presence and extensive collaborations with other scholars. Prominent articles on AR-related topics are distributed across indexed journals. The keyword trend analysis suggests that future research should shift from mere implementation in learning contexts toward optimizing the learning environment through rigorous evaluation of AR effectiveness in education.